Integrating Sustainability in Business: An Essential Need in the Global Context - Radulescu, Carmen Valentina; Popescu, Loredana; Badea, Carmen Georgiana (European Journal of Sustainable Development, 2018)
In the context of globalization and sustainable development requirements reconfigures all aspects of social and economic life so as to remove disincentives for progress towards a society that recognizes the importance of capitalization not only economically but also in terms of human resources and natural resources. We started this research building on the general and specific trends identified as being relevant for integrating business sustainability: increasing inequality in revenue; decoupling economic growth from the opportunity to generate income through job creation, endangering the primary distribution of well-being; intensifying geostrategic competition; increasing pollution in developing countries; the manifestation of the impact of climate change through extreme weather phenomena and the diminution of water resources; increasing companies' contribution to addressing general development issues and increasing consumer demand for sustainable performance. In this context, I start with addressing and clarifying the concept of sustainable business, which is becoming more and more individualized in the global economy, its promotion and development becoming a flagship feature for many companies and I will continue with identifying and analyzing managerial strategies and tools. Keywords: sustainable development; sustainability strategies; business; innovation.